ETOS KERJA TUTOR DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM)BINA KREASI KECAMATAN TENAYAN RAYAKOTA PEKANBARU - Annisa, Novia; Ayub, Daeng; Achmad, Said Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: the formulation of the problem in this study is "How is the work ethic of the tutor at the Community Learning Activity Center (CLAC) Bina Kreasi District of Tenayan Raya of Pekanbaru city". This study uses descriptive naturalistic research with a qualitative approach that aims to provide a systematic description of the work ethic of tutors at the Community Learning Activity Center (CLAC) Bina Kreasi District of Tenayan Raya City, Pekanbaru. This study consists of one variable, namely work ethic with 3 indicators, that is (1) Work attitude (2) Work spirit (3) Work discipline. The subjects of this study is 3 people who were class tutors at CLAC Bina Kreasi. Data collection techniques used are by conducting observations, interviews, and documentation. Based on the results of interviews with informants, the researchers found data that through these 3 indicators it can be seen that the work ethic of tutors at the Community Learning Activity Center (CLAC) Bina Kreasi District of Tenayan Raya Kota Pekanbaru is that tutors always want to give the best for their work by assessing and improving deficiency. Tutors are always passionate about work. tutor work discipline.Keywords: work ethic, tutor